2017
DOI: 10.1038/s41598-017-05742-x
|View full text |Cite
|
Sign up to set email alerts
|

Generation of spin waves by a train of fs-laser pulses: a novel approach for tuning magnon wavelength

Abstract: Currently spin waves are considered for computation and data processing as an alternative to charge currents. Generation of spin waves by ultrashort laser pulses provides several important advances with respect to conventional approaches using microwaves. In particular, focused laser spot works as a point source for spin waves and allows for directional control of spin waves and switching between their different types. For further progress in this direction it is important to manipulate with the spectrum of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 31 publications
0
50
0
1
Order By: Relevance
“…In experiments described in [29,30] the optical pumping was realized in thin bismuth iron-garnet films [33] excited magnetic field h was about 10 Oe, so the bandgap was very small and due to the damping no Floquet states were observed. But the pump incidence angle was 17°, and main effect of amplitude increasing was from the right part of Eq.…”
Section: Figure 1 Excitation Of the Magnetization Precession In An Imentioning
confidence: 99%
See 1 more Smart Citation
“…In experiments described in [29,30] the optical pumping was realized in thin bismuth iron-garnet films [33] excited magnetic field h was about 10 Oe, so the bandgap was very small and due to the damping no Floquet states were observed. But the pump incidence angle was 17°, and main effect of amplitude increasing was from the right part of Eq.…”
Section: Figure 1 Excitation Of the Magnetization Precession In An Imentioning
confidence: 99%
“…Recently, influence of the periodic pumping has been demonstrated [29,30]. It was shown that a train of optical pump pulses can drive the magnetization within the illuminated area thereby exciting spin waves and their amplitude can be significantly increased if the magnetization oscillation frequency synchronized with the laser pulses.…”
Section: Introductionmentioning
confidence: 99%
“…The inverse Faraday effect (IFE) provides a new way for efficient control of spins at GHz and THz rates 1 . Circularly polarized laser pulses can induce the IFE effective magnetic field of about 10 2 -10 4 Oe in a magnetic dielectric and excite the magnetization precession leading to magnetostatic spin waves [9][10][11][12][13][14][15][16][17][18] . By now, the IFE has been investigated only in a freestanding crystals and films on a substrate.…”
Section: Introductionmentioning
confidence: 99%
“…First of all, it allows to influence on the magnetization locally, within the focused laser spot, that can be easily shifted along the sample [11,12]. The micron size area of the sample where spins interact with photons can operate like a point source of magnons [13][14][15] . Variation of the laser spot shape and size provides tunability in terms of the type and spectrum of the generated spin waves.…”
Section: Introductionmentioning
confidence: 99%
“…For example, one could switch between surface and backward volume spin waves by simply reducing diameter of the laser spot [16,17]. Moreover, passing from excitation with a single pulse to the multiple pulse excitation gives additional degree of freedom leading to enhancement of the spin waves amplitude, tunability of their spectrum and directivity of the magnon source [14,15].…”
Section: Introductionmentioning
confidence: 99%